Anatomical and functional overlap within the insula and anterior cingulate cortex during interoception and phobic symptom provocation. Issue 5 (8th December 2011) - Caseras, Xavier; Murphy, Kevin; Mataix‐Cols, David; López‐Solà, Marina; Soriano‐Mas, Carles; Ortriz, Hector; Pujol, Jesus; Torrubia, Rafael
Abstract The anterior insula and the dorsal anterior cingulate cortex (ACC) are regarded as key brain structures associated with the integration of perceived phobic characteristics of external stimuli and the perception of ones own body responses that leads to emotional feelings. To test to what extent the activity in these two brain structures anatomically and functionally overlap during phobic reactions and interoception, we submitted the same group of phobic participants (n = 29; either spider or blood‐injection‐injury (BII) phobics) and controls (n = 17) to both type of experimental paradigms. Results showed that there was a clear anatomical overlap in the Blood Oxygen Level‐Dependent (BOLD) responses within the anterior insula and ACC elicited during phobic symptom provocation and during interoceptive awareness. The activity within these two brain structures also showed to be correlated in the spider phobia group, but not in the BII phobic participants. Our results seem to support the idea that the activity within these two brain areas would be associated with the integration of perceived stimuli characteristics and bodily responses that lead to what we label as "fear." However, that seems not to be the case in BII phobia, where more research is needed in order to clarify to what extent that could be associated with the idiosyncratic physiological response that these patients present in front of phobic stimuli (i.e., drop in heart rate and blood pressure). Hum Brain Mapp, 2013. © 2011 Wiley Periodicals, Inc.